A high-stability neutron generator for industrial online elemental analysis - Xiang-quan Chen; Lei Xiong; Hui Xie; Jing-fu Guo; Xue-ming Zhang; Yong-jun Dong (Nuclear Engineering and Technology, 2024)
The yield stability of the neutron generator directly affects the accuracy of elemental analysis. This paper presents an industrial fully automatic neutron generator with a 48 mm neutron tube based on PLC to improve the stability and reliability of the neutron generator in industrial applications. By integrating a Kalman Filter with the PID algorithm in a PLC, the neutron yield of the generator is remarkably stabilized, achieving 1 × 108n/s. The neutron generator has been employed for industrial online elemental analysis. The results demonstrate that only a slight fluctuation of ±0.82 % exists in the neutron yield, and the reproducibility of the generator holds at a significant level of 0.05. This improved neutron generator can be applied to the online bulk analysis of carbon in coal-fired power stations and absolute measurement of neutron source emission rate.